Interior Design trajectory from the perspective of professionalization - Glória Barbosa, Paula; Safar, Giselle Hissa; Carpintero Rezende, Edson José (Convergences - Journal of Research and Arts Education, 2023)
The history of Interior Design can be told under different aspects. It can be told through the biography of prominent professionals, the production of decorative arts, in the relationship with architecture and the plastic arts, among many other possibilities. This work analyzes the main transformations experienced by the activity in its professionalization process. Therefore, it was essential to briefly understand the historical context in which this evolution took place, highlighting the French of the 17th and 18th centuries, the English of the 18th and 19th centuries and the American of the 20th century, which made these countries, each in its own time, led the professionalization of Interior Design. These influential contexts have become a mirror for the development of the profession in several countries, including Brazil.